1998
DOI: 10.1080/095003498150231
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gain and noise performance of bidirectionally pumped Pr 3+ -doped fluoride fibre amplifier configurations with unbalanced pumping

Abstract: An alysis of gain an d n oise pe rform an c e of bid ire c tion ally pu m pe d Pr 3+ -d ope d¯u orid e ® bre am pli® e r c on ® gu ration s w ith u n balan c e d pu m pin g Abs trac t.This paper presents a numerical study of the performance of asymmetric bidirectionally pumped and re¯ective-type ampli® er con® gurations in the unsaturated and saturated regions. The dependences of the optimum relative backward pump power on the ® bre parameters and on the ampli® er's working conditions for each con® guration ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The authors observed that the doping concentration of around 1000 ppm results into significant degradation in performance [23]. Valles et al proposed a numerical study to evaluate the gain and ASE performance of PDFA based on fluoride fiber and bidirectional pumping [24]. A peak small-signal gain of around 31 dB is obtained by using a double-path configuration with a reflective type of mirror.…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed that the doping concentration of around 1000 ppm results into significant degradation in performance [23]. Valles et al proposed a numerical study to evaluate the gain and ASE performance of PDFA based on fluoride fiber and bidirectional pumping [24]. A peak small-signal gain of around 31 dB is obtained by using a double-path configuration with a reflective type of mirror.…”
Section: Introductionmentioning
confidence: 99%